Let's talk about sex: lower limb amputation, sexual functioning and sexual well‐being: a qualitative study of the partner's perspective. Issue 23 (December 2013) - Verschuren, Jesse EA; Zhdanova, Mariya A; Geertzen, Jan HB; Enzlin, Paul; Dijkstra, Pieter U; Dekker, Rienk
Abstract : Aims and objectives: To describe the impact of patients' lower limb amputations on their partners' sexual functioning and well‐being. Background: Annually, about 3300 major lower limb amputations are performed in the Netherlands. An amputation may induce limitations in performing marital activities, including expression of sexual feelings between partners. However, up until now, little attention has been paid towards this aspect in both research and clinical practice. The lack of studies on sexual activities and lower limb amputation is even more apparent with respect to partners of patients with such an amputation. Previous studies have shown, however, that the presence of a disease or disability may have a large impact not only on the patient's but also on the partner's sexual activities. Design: Qualitative thematic analysis. Methods: Semi‐structured interviews. The questions used in the interview were inspired by a generic framework about chronic disease and sexual functioning and well‐being. In total, 16 partners of patients with a lower limb amputation who were at least 18 years old were recruited in different rehabilitation centres. Results: Seven major themes (i.e. importance of sexuality, thoughts about sexuality before the amputation, changes in sexual functioning and sexual well‐being, amputation as the main cause of these changes, acceptance of the amputation, role confusion and communication about sexuality) were derived from the interviews. Minor changes in sexual functioning and sexual well‐being were reported by the participants. Problems participants did encounter were solved by the couples themselves. For some participants, their sexual well‐being improved after the amputation. Conclusion and relevance to clinical practice: Participants in our study reported minor changes in their sexual well‐being. Most of them indicated that communication about the changes expected and how to cope with these would have been helpful. It is therefore important that professionals address sexuality during the rehabilitation process with patients and partners.